The Comparative Review of The Impact of Education and Health Expenditures on The Human Development Index in South Kalimantan and Central Kalimantan - M Muzdalifah (International Journal of Southeast Asian Studies (IJSAS), 2021)
The study was motivated by the achievement of HDI delivered a second neighbouring province; one of the provinces is older than the other province. The achievement of HDI of the senior provinces is always below the junior province. This research is quantitative descriptive, conducted in 13 districts/cities in South Kalimantan and 14 regencies/cities in Central Kalimantan for the 2010-2018 period. The data used are secondary data obtained from the Central Statistics Agency, analyzed by the panel data regression. The results of the study show that education and health expenditures have significant effects on HDI in South Kalimantan. The variable of health expenditure positively correlated to the HDI, while the education spending variables correlated negatively. The two variables not significantly affect Central Kalimantan. The quality of regional expenditures is what proxies by the flypaper effect phenomenon as the chosen approach. The findings of the research in the two provinces show that there is a phenomenon of the paper effect phenomenon, which means that the regional expenditures in these two provinces are not qualified yet, so the effect has not been felt optimally.